Spectral quality of photo-selective shade nettings improves antioxidants and overall quality in selected fresh produce after postharvest storage. Issue 3 (3rd April 2018) - Sivakumar, Dharini; Jifon, Johan; Soundy, Puffy
ABSTRACT: Growing vegetables under shade nets is currently becoming popular in summer to provide protection from high intensities of light. High temperatures and light quality affect postharvest quality and storage life of vegetables. Photo-selective shade netting technology is an emerging agro-technological concept that aims at the improvement of crop quality by the modification of spectral light and provides physical protection of the crop. Incorporation of various light-dispersive and reflective chromatic additives in the photo-selective nets is responsible for the modification of spectral quality, especially in the UV 200–400 nm, visible (400–700 nm), or far-red (FR; also known as "near infrared"; 705–740 nm) in the infrared region of the spectral region. Altered light-quality changes under the photo-selective nets were shown to improve the accumulation of phytochemicals and aroma compounds, and ultimately, the growth, yield, and quality of the selected vegetables such as tomatoes, sweet peppers, lettuce, and aromatic herbs. The postharvest quality of fresh produce is also influenced by environmental conditions such as light, average temperature, minimum temperature, and day-night temperature differences. During production, light quality under the photo-selective shade nets had a positive effect on the quality parameters and phytochemical content in fresh produce after postharvest storage. The review includes the use of photo-selective netting in protected agriculture as a preharvest tool to improve aroma volatiles, antioxidants, and overall quality of fresh produce after postharvest storage.